2003
DOI: 10.1073/pnas.0337480100
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampus mediates glucocorticoid-induced impairment of spatial memory retrieval: Dependence on the basolateral amygdala

Abstract: Previous studies have indicated that stress-activated glucocorticoid hormones induce temporary memory retrieval impairment. The present study examined whether adrenal steroid receptors in the hippocampus mediate such glucocorticoid effects on spatial memory retrieval. The specific glucocorticoid receptor (GR) agonist 11␤, 17␤-dihydroxy-6,21-dimethyl-17␣-pregna-4,6-trien-20yn-3-one (RU 28362; 5 or 15 ng) infused into the hippocampus of male Sprague-Dawley rats 60 min before water-maze retention testing, 24 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
162
4
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(183 citation statements)
references
References 75 publications
12
162
4
5
Order By: Relevance
“…Roozendaal and McGaugh found that lesions of the amygdala do not necessarily result in memory impairment but block stress hormone effects on memory consolidation. This is because the amygdala interacts with other brain regions including the hippocampus and mPFC, to regulate stress hormone effects on memory (Roozendaal et al, 2002;Roozendaal, 2003). In addition, the GABAergic intercalated cells of the amygdala, which receive input from the mPFC and control amygdala input, exhibit NMDA-dependent long-term potentiation (Royer and Pare, 2002).…”
Section: Amygdaloid Glutamate Nmda Receptors Participate In the Modulmentioning
confidence: 99%
See 1 more Smart Citation
“…Roozendaal and McGaugh found that lesions of the amygdala do not necessarily result in memory impairment but block stress hormone effects on memory consolidation. This is because the amygdala interacts with other brain regions including the hippocampus and mPFC, to regulate stress hormone effects on memory (Roozendaal et al, 2002;Roozendaal, 2003). In addition, the GABAergic intercalated cells of the amygdala, which receive input from the mPFC and control amygdala input, exhibit NMDA-dependent long-term potentiation (Royer and Pare, 2002).…”
Section: Amygdaloid Glutamate Nmda Receptors Participate In the Modulmentioning
confidence: 99%
“…Systemic administration of the glucocorticoid synthesis inhibitor metyrapone attenuated the long-term expression of contextual fear conditioning in a dose-dependent manner (Cordero et al, 2002). Roozendaal and McGaugh indicated that glucocorticoids could act directly in the amygdala to influence memory consolidation (Roozendaal and McGaugh, 1997;Roozendaal et al, 2002;Roozendaal, 2003). It is remarkable that glucocorticoids also participate in the extinction of conditioned fear.…”
Section: Introductionmentioning
confidence: 99%
“…The neural connectivity of pons with HPC, Amyg and PFC may be essential for regulation of neuronal circuits associated with sleep-related functions [52,54,60]. Impairments in performance after sleep loss could be attributed to the changes in functional connectivity in various neural networks [61,62] and it could also be due to neurons going offline at local level [63].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that post-training injections of the synthetic glucocorticoid dexamethasone enhanced the performance in a 48-h inhibitory avoidance retention test, and that a selective Nmethyl-d-aspartate (NMDA)-induced lesion of the BLA blocked this enhancement . In another task, intrahippocampal infusions of a glucocorticoid receptors (GRs) agonist (RU 28362) given 60 min before a spatial task retention test impaired retrieval (Roozendaal et al, 2003) and a selective NMDA-induced lesion of the BLA 1 week before training blocked this impairment. Likewise, post-training microinfusions of norepinephrine or the beta-noradrenergic antagonist propranolol into the BLA immediately following training in a spatial version of the water maze task was also shown to modulate spatial performance.…”
Section: Amygdalar Mediation Of the Effects Of The Stress Hor-monementioning
confidence: 99%